Factors Influencing Consumer Buying Behaviour for Electric Two-Wheeler Vehicles in Kathmandu Valley - Dongol, Padam; Dangol, Raunak (MVIC Journal of Management and Information Technology, 2025)
This study aims to investigate the factors influencing consumer buying behavior for electric two-wheelers in Kathmandu Valley through a quantitative research approach. Primary data were gathered using structured questionnaires, distributed to selected customers within the region. A nonprobability convenience sampling method was employed, with 82 questionnaires distributed and 50 completed responses returned, yielding a response rate of 60.97%. The data collected were analyzed using descriptive statistics, utilizing SPSS software to generate frequency distributions, means, standard deviations, and visual representations such as graphs and pie charts. The demographic analysis of respondents revealed that 64% were female, with the majority aged between 21-25 years (42%). Most respondents had completed intermediate (+2) education (30%), with 36% being students. Income levels varied, with the majority earning between Rs 100,000 to 300,000 (30%). The study found that education and consumer behavior showed the highest uniformity, with education having a mean of 3.724 and a low standard deviation of 0.611. Consumer behavior exhibited the lowest variation among respondents, with a mean of 3.016 and a standard deviation of 0.537. The data suggests moderate consistency across most demographic variables, with notable uniformity in educational background and consumer behavior patterns.